Environmental stressors may cause unpredicted, notably lagged life-history responses in adults of the planktivorous Atlantic herring. (February 2020) - dos Santos Schmidt, Thassya C.; Devine, Jennifer A.; Slotte, Aril; Claireaux, Marion; Johannessen, Arne; Enberg, Katja; Óskarsson, Gudmundur J.; Kennedy, James; Kurita, Yutaka; Kjesbu, Olav Sigurd
Highlights: Energy allocation patterns in herring are tightly coupled to ecosystem status. Herring prioritizes body weight rather than body length to maintain body condition. Herring shows highly complex interannual trade-offs between fecundity and egg size. Oocyte development may start almost one month earlier or proceed faster. Abstract: Here we challenge traditional views on the direction of change in teleost body condition and reproductive traits in response to abiotic and biotic factors by studying the data-rich, planktivorous Norwegian spring-spawning herring (NSSH), a member of the abundant Atlantic herring ( Clupea harengus ) stock complex. To test potential influential factors, we focused on the last twenty years, i.e. a period with ocean warming, a transient but significant drop in zooplankton biomass, and accelerating interspecific competition resulting from primarily Atlantic mackerel ( Scomber scombrus ) entering these high-latitude waters in large quantities, "the new mackerel era" in the Nordic Seas. Adult NSSH concurrently allocated relatively less to growth in length than weight resulting in higher body condition. Growth likely decreased in warmer waters under stiff prey competition to support reproductive costs. Condition and reproductive responses were not only immediate but were also lagged by three seasons, corresponding to the period when new oocytes are produced. Furthermore, fecundity increased in warmer waters while egg size dropped. Hence, fine-tuned trade-off mechanisms were apparent and varied. We demonstrate that evaluations of reproductive trade-offs based on pooled data are misleading; poor- and good-condition NSSH followed different reproductive trajectories. These findings emphasize difficult-to-predict trends in life-history traits should be tracked longitudinally by the individuals and their aggregate cohort, as they are linked to complex overarching environmental phenomena, like ecosystem carrying capacity and climate fluctuations.